Effect of La and Mo co-doping on the properties of AgSnO2 contact material. (9th July 2021) - Wang, Jingqin; Chang, Yongqiang; Zhu, Yancai; Zhang, Guangzhi; Huang, Guanglin
Abstract: For the shortage of the AgSnO2 contact material, the models of SnO2, La–SnO2, Mo–SnO2, and La–Mo–SnO2 were built to calculate their electrical and mechanical properties based on the first principles of density functional theory in this study. The La-Mo co-coped SnO2 is the most stable of all the models according to the enthalpy change and the impurity formation energy. By analyzing the energy band structure and density of states, the doped models are still the direct bandgap semiconductor materials. The valence band moves up and the conduction band moves down after doped, reducing the band gap and enhancing the conductivity. With the reduced energy for carrier transition, the electrical performance of La-Mo co-doped SnO2 is improved best. The mechanical properties of SnO2 were completely improved by La-Mo co-doping with the calculation results. The doped SnO2 materials were prepared by sol-gel method and the doped AgSnO2 materials were prepared by powder metallurgy method. The x-ray diffraction experiment, hardness, conductivity and wettability experiment had been taken. And the experimental results show that the AgSnO2 can be improved comprehensively by La-Mo co-doping, verifying the conclusions of the simulation. It provides an effective method for the preparation of high-performance contact materials.